Characterization of Electrospun Poly(ε-caprolactone) Nano/Micro Fibrous Membrane as Scaffolds in Tissue Engineering: Effects of the Type of Collector Used - Dianney Clavijo-Grimaldo; Ciro Alfonso Casadiego-Torrado; Juan Villalobos-Elías; Adolfo Ocampo-Páramo; Magreth Torres-Parada (Membranes, 2022)
Electrospinning is an electrohydrodynamic technique that transforms a polymer solution into nano/microscopic diameter fibers under the influence of a high-voltage electric field. Its use in the fabrication of nano/micro fibrous membranes as scaffolds for tissue engineering has increased rapidly in recent years due to its efficiency and reproducibility. The objective of this study is to show how the use of the same polymeric solution (polycaprolactone 9% w/v in chloroform: isopropanol 50:50) and identical electrohydrodynamic deposition parameters produces fibers with different characteristics using a flat collector platform with movements in the X and Y axes vs. a conventional rotary collector. The manufactured nano/microfibers show significant differences in most of their characteristics (morphology, roughness, hydrophilicity, and mechanical properties). Regarding the diameter and porosity of the fibers, the results were similar. Given that scaffolds must be designed to guarantee adequate survival and the proliferation and migration of a certain cell type, in this study we analyze how the variations in the characteristics of the fibers obtained are essential to defining their potential application.